Issues and Challenges Related to Digital Equity - Resta, Paul; Laferrière, Thérèse (International Handbook of Information Technology in Primary and Secondary Education, 2008)
Although there has been significant growth worldwide in access to computers and the Internet, the digital divide continues to be a major form of social and economic exclusion for many peoples across the globe. This section focuses on research related to digital-related issues and challenges encountered in the field of primary and secondary education. Five issues and related challenges and possible strategies are identified: 1) access to hardware, software and connectivity to the Internet; 2) access to meaningful, high quality, culturally relevant content in local languages; 3) access to educators who know how to use digital tools and resources; 4) access to high quality research on the application of digital technologies to enhance learning; 5) access to content creation.
Keywords: TICE; numérique